Souq Waqif And Its Approach Toward Sustainable Cultural Tourism (Journal of Namibian Studies : History Politics Culture, 2023)
The 2030 Agenda for Sustainable Development highlighted the role of culture in sustainable development worldwide. Consequently, recently the concept of sustainable cultural tourism has become increasingly important. UNESCO identified five significant sustainable development targets in culture, which are protecting cultural heritage, transferring knowledge and experience, promoting creativity and artistic innovation, promoting cultural education, and promoting understanding and tolerance. The five targets also emphasize the importance of cultural heritage preservation and presentation for future generations.Following the global interest in sustainable cultural tourism, Souq Waqif in Doha organized programs that would contribute to keeping the traditions, customs, and cultural values that characterize society’s identity. This article examines Souq Waqif’s practice, which is contextualized within a long process to regain its historical and heritage values and meanings. The article will explore the aims, plans, and influences on society of eco-friendly cultural tourism.